Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Pada Bank Yang Terdaftar Di BEI Tahun 2018-2020 - Ahmad Abi Dardak; Budi Wahono; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to find out how the influence of Good Corporate Governance on the financial performance of banks listed on the IDX in 2018-2020. The population in this study were all banking companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sample used in this study were banking companies listed on the Indonesia Stock Exchange for the period 2018-2020 using the purposive sampling method, as many as 25 company. The results of the study show that: 1) There is a simultaneous effect of the board of commissioners, institutional ownership, independent commissioners, audit committee and board of directors on banking financial performance. 2) There is a partial effect of the board of commissioners on the financial performance of banks. 3) There is no partial effect of institutional ownership on banking financial performance. 4) There is partial influence of independent commissioners on banking financial performance. 5) There is no effect of the audit committee on the financial performance of banks. 6) There is a partial effect of the board of directors on the financial performance of banks.. Keyword: Good Corporate Governance, Kinerja Keuanagan, Return Aset (ROA)